English Nonverbal Expressions in Communication (Eurasian Scientific Herald, 2023)
Humans send messages not only with the help of of words, but they can also convey meaning through the usage of facial expressions, eye contact, body language, hand gestures and tone of voice all of which we know as nonverbal communication